(untitled) (Journal of NELTA, 2024)
Teacher emotion is a relatively less explored area in the context of English language education research in general and teacher professional identity in particular. This study reports the emotional experiences of four secondary-level English language teachers from public schools in Nepal, exploring their life stories through informal conversations and in-depth interviews. Thematic analysis of their life stories indicated that as a roller coaster ride, teachers underwent positive, happy, and exciting moments to negative emotional experiences like sadness, dissatisfaction, humiliation, and vulnerability influencing their becoming. Vulnerability emerged as significant motif in their stories, which, though generally considered a negative emotion, immensely contributed to teachers’ development. In addition, emotional attachment with students, colleagues, and school; compliment and appreciation by colleagues,parents, and students; and students’ success and satisfaction enhanced self-esteem and commitment to teaching, positively contributing to identity construction. In contrast, sad and depressing moments arising from students’ disruptive behaviour, exclusion of teachers in crucial decision-making, and misrepresentation and misrecognition of their contributions by seniors and administrators in their discourses posed a crisis on their identity, stimulating feelings like quitting the job. The study’s findings implied an urge to pay due consideration to the affective dimension of teachers by policymakers and administrators for their professional development and identity construction, thereby enhancing students’ learning outcomes.